Islamic Law, Human Rights, and Democracy from an Islamic Perspective - Winda Prameswari Prabowo; Nurjaya Nurjaya; Sumarta Sumarta; Kusyana Kusyana (Penerbit Hellow Pustaka, 2025)
This study aims to analyze the Islamic perspective on Islamic Law, Human Rights, and Democracy. Specifically, it explores the fundamental principles within Islamic teachings that address justice, equality, and human dignity. The research employs a qualitative library study design, involving the analysis of primary religious texts such as the Qur’an and Sunnah, as well as relevant secondary literature. The main findings indicate that Islam contains principles that can be interpreted as compatible with modern human rights concepts and democratic governance. The concept of shura (consultation) and maqasid al-shariah emphasize the importance of public participation and human welfare. Fundamental rights such as the right to life, freedom of religion, and the right to justice are also explicitly recognized within Islamic tradition. However, this study also identifies areas of tension and diverse interpretations within Islamic thought regarding these concepts, particularly in their practical implementation in many Muslim-majority countries. A comparison with the Universal Declaration of Human Rights reveals significant points of convergence, despite differences in philosophical foundations. The implications of this study lie in providing a nuanced understanding of the complex relationship between Islamic Law, human rights, and democracy from an Islamic perspective, highlighting both their potential compatibility and the challenges of implementation. Such understanding is crucial for intercultural dialogue and for developing appropriate governance models in Muslim-majority societies. The originality of this research lies in its systematic effort to bridge the discourse on Islamic Law, human rights, and democracy within a unified analytical framework, offering a comprehensive perspective that not only identifies areas of alignment but also critically addresses tensions and interpretative diversity within Islamic tradition.